2014
DOI: 10.1155/2014/341270
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of 3-Rhamnosylquercetin, a Glycosylated Form of Quercetin, against the Myotoxic and Edematogenic Effects of sPLA2fromCrotalus durissus terrificus

Abstract: This paper shows the results of quercitrin effects on the structure and biological activity of secretory phospholipase (sPLA2) from Crotalus durissus terrificus, which is the main toxin involved in the pharmacological effects of this snake venom. According to our mass spectrometry and circular dichroism results, quercetin was able to promote a chemical modification of some amino acid residues and modify the secondary structure of C. d. terrificus sPLA2. Moreover, molecular docking studies showed that quercitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…There are studies that have evaluated the effect of flavonoids and glycosylated flavonoids on the course of the enzymatic and pharmacological activity of secretory phospholipases A2 [ 5 , 6 ]. Moreover, these studies deserve further efforts to elucidate the mechanism of action of these types of flavonoids on sPLA2, including studies of the conformational changes of flavonoids that modify their antioxidant properties to pro-oxidants, and these mechanisms should be better understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies that have evaluated the effect of flavonoids and glycosylated flavonoids on the course of the enzymatic and pharmacological activity of secretory phospholipases A2 [ 5 , 6 ]. Moreover, these studies deserve further efforts to elucidate the mechanism of action of these types of flavonoids on sPLA2, including studies of the conformational changes of flavonoids that modify their antioxidant properties to pro-oxidants, and these mechanisms should be better understood.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, sPLA2 in snake venom is an attractive therapeutic target due to its accessibility, ease of purification and, in the case of sPLA2 in humans, high levels of systemic enzymatic activity, which characterize and contribute to most of the inflammatory disorders, including neurodegenerative diseases. Therefore, the discovery of new inhibitors of sPLA2 is essential to produce new safe and effective drugs with fewer side effects compared to the current therapy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The edematogenic assay performed with Edema Induced by sPLA2 from Crotalus durissus terrificus Involves PLC and PKC Signaling… DOI: http://dx.doi.org/10.5772/intechopen.80848 native sPLA2 and 5CQA incubated with sPLA2 clearly showed that edema induced by sPLA2:5CQA was not abolished, but significantly diminished ( Figure 4A). Thus, in part, the anti-inflammatory effect of 5CQA probably involves the downregulation of pharmacological and enzymatic activity of sPLA2 [57,58]. In Figure 3B, we show the effect of p-bromophenacyl bromide (p-BPB) and umbelliferone (7-HOC) on edema induced by sPLA2.…”
Section: "To Be or Not To Be" Enzymatically Active Important For Cdt mentioning
confidence: 93%
“…Quercetin-3- O -arabinoside: 1 H-NMR (300 MHz, CD 3 OD) δ 6.41 (d, J = 2.1 Hz, H-6), δ 6.23 (d, J = 2.1 Hz, H-8), δ 7.51 (d, J = 2.0 Hz, H-2′), δ 6.85 (d, J = 8.3 Hz, H-5′), δ 7.25 (dd, J = 8.3 Hz and 2.0 Hz, H-6′), δ 5.27 (d, J = 5.1 Hz, H-1″), δ 3.23–3.62 (H-2″–H-5″); 13 C NMR (75 MHz, CD 3 OD) 156.1 (C-2), 133.5 (C-3), 177.3 (C-4), 161.1 (C-5), 98.5 (C-6), 164.3 (C-7), 93.4 (C-8), 155.9 (C-9), 103.5 (C-10), 120.3 (C-1′), 115.3 (C-2′), 145.3 (C-3′), 148.7 (C-4′), 115.7 (C-5′), 123.0 (C-6′), 100.9 (C-1″), 70.5 (C-2″), 71.4 (C-3″), 65.5 (C-4″), 63.6 (C-5″) [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Quercetin-3- O -rhamnoside (Quercitrin): 1 H-NMR (300 MHz, CD 3 OD) δ 6.37 (d, J = 2.1 Hz, H-6), δ 6.19 (d, J = 2.1 Hz, H-8), δ 7.34 (d, J = 2.1 Hz, H-2′), δ 6.94 (d, J = 8.7 Hz, H-5′), δ 7.30 (dd, J = 8.4 Hz and 2.1 Hz, H-6′), δ 5.34 (d, J = 1.5 Hz, H-1″), δ 4.23 (dd, J = 3.0 Hz and 1.8 Hz, H-2″), δ 3.75 (dd, J = 9.0 Hz and 3.3 Hz, H-3″), δ 3.32 (dd, J = 9.3 Hz and 3.3 Hz, H-4″), δ 3.41 (d, J = 6.0 Hz, H-5″), δ 0.94 (d, J = 6.0 Hz, H-6″); 13 C NMR (75 MHz, CD 3 OD) 159.2 (C-2), 136.5 (C-3), 179.7 (C-4), 163.1 (C-5), 99.8 (C-6), 165.8 (C-7), 94.9 (C-8), 158.8 (C-9), 106.2 (C-10), 123.1 (C-1′), 117.3 (C-2′), 146.7 (C-3′), 149.8 (C-4′), 116.7 (C-5′), 123.3 (C-6′), 103.5 (C-1″), 72.2 (C-2″), 72.1 (C-3″), 73.4 (C-4″), 72.0 (C-5″), 17.7 (C-6″) [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%